Piano sonata no. 14 in C# minor, op. 27, no. 2 (Cramer, Beale, & Co.) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (United Kingdom; London; Cramer, Beale & Co.)
Piano sonata no. 14 in C# Minor, op. 27, no. 2, edited by Moscheles; Reprint of the edition published by Cramer, Addison, & Beale ca. 1834-1839